The active welfare state - Langendonck, Jef Van (Revista Brasileira de Direitos Fundamentais & Justiça, 2008)
This article briefly presents an overview of the evolution of both the social security and Welfare State's concepts, in order to thoroughly examine the relations between social security and rights to labor and to a freely chosen occupation. Some cases are then presented, to better show the importance of such rights for the new configuration of social security: the Active Welfare State.